Study of Biocrudes Obtained via Hydrothermal Liquefaction (HTL) of Wild Alga Consortium under Different Conditions - Caroline Barrère-Mangote (Processes, 2021)
Microalga-based fuels are promising solutions for replacing fossil fuels. This feedstock presents several advantages such as fast growth in a harsh environment and an ability to trap gases emitted from industries, thus reducing global warming effects. An efficient way to convert harvested microalgae into biofuels is hydrothermal liquefaction (HTL), which yields an intermediate product called biocrude. In this study, the elemental and molecular compositions of 15 different HTL biocrudes were determined by means of different techniques. Wild algae were cultivated in an industrial environment with plant emissions as a carbon source in fresh or seawater. It was notably observed that the culture medium had an influence on the biochemical composition and mineral matter content of algae. Thus, seawater algae were characterized by larger amounts of carbohydrates and mineral matter than freshwater ones, which also affected the oil yields and the light and heavy fractions of biocrudes.